Công văn của Ủy ban Dân tộc về việc trả lời chất vấn của đại biểu Quốc hội (Số: 1244/UBDT-PC) - Ủy ban Dân tộc (2017)
Công văn của Ủy ban Dân tộc về việc trả lời chất vấn của đại biểu Quốc hội (Số: 1244/UBDT-PC) ngày 14/11/2017